Vilnius Graffiti from the Late Soviet Era to 2022: Stages of Development and the Social Profile of the Graffiti Community (Relevant Tomorrow / Aktualu rytoj, 2022)
To broaden the scope and depth of knowledge about the less explored peripheral graffiti communities, the article presents a comprehensive case study of Vilnius graffiti from the late Soviet era to 2022. It examines the aspects of the historical development and social structure, as well as the characteristics of graffiti as an illegal form of visual expression, its content and relationship to urban space, and its chronological progress from the late Soviet era to 2022. Using an extensive review of the academic literature on graffiti communities and a qualitative study carried out in 2007-2022 and based on semi-structured in-depth interviews and analysis of other sources, I dentify four chronological stages of the development of the graffiti subculture in Vilnius: the early (pre-1990) stage, the incubation period (1990-2000), the golden age (2000-2010), and the period of low tide (post-2010). The research has also showed that the social structure of the Vilnius graffiti artists’ community is characterized by a high degree of socio-ethnic heterogeneity and a fairly high degree of gender homogeneity (male dominance). It has been noted that over time, the graffiti community, a subcultural group that unites adolescents and young people, has become increasingly diverse in terms of age. An aging trend of the community has been observed.
Keywords: graffiti; urban space; Vilnius; sociology of space; subculture; late Soviet era; Lithuanian independence period (post-1990)